PENGGUNAAN MEDIA INOVATIF UNTUK MENINGKATKAN MOTIVASI DAN PARTISIPASI BELAJAR PESERTA DIDIK PADA MATA PELAJARAN PENDIDIKAN AGAMA KRISTEN DAN BUDI PEKERTI KELAS 3 UPTD SD NEGERI ANGKASA PENFUI - Sherly Yunita Faot (Institut Agama Kristen Negeri Kupang, 2023)
This study aims to increase the motivation and learning participation of students in learning PAK and BP class 3 UPTD SD Negeri Angkasa Penfui. This research is a classroom action research conducted in two cycles, each cycle consisting of one meeting. In the implementation of cycle I, it was carried out using innovative media in the form of learning videos and song creations in the order of creation. Cycle II was carried out using innovative media in the form of learning videos, creation of song creation sequences and joy lot games. Data collection techniques through observation sheets of students' motivation and learning participation during the learning process and documentation of activities. The results showed that: (1) The learning motivation of students in class 3 PAK and BP learning by using innovative media in the first cycle was 2.4 in the sufficient category and in the second cycle it increased to 3.7 in the good category; (2) The learning participation of students in class 3 PAK and BP learning by using innovative media in cycle I was 2.3 categories sufficient and cycle II increased to 3.6 categories good. Thus the use of innovative media in the form of learning videos, creation of song creations and joy lot games succeeded in increasing the motivation and learning participation of students in learning PAK and BP class 3 UPTD SD Negeri Angkasa Penfui.